Transformation of Language, Literature and Technology in Learning - Hidayat, Rahman (Transpublika Publisher, 2024)
This study aims to implement the transformation of language, literature and technology views in learning (transportation). The research method uses the Systematic Literature Review (SLR) Prism Method. The results of the study produced 8,675 similar articles, then a screening was carried out so that 3 articles were left ready to use. The first article discusses building height estimation using deep learning-based street view imagery, the second article proposes the design of an Internet of Things (IoT)-based intelligent transportation system to support smart cities, and the third article explores the role of e-learning in enhancing green innovation and technology for sustainable management practices. This research highlights the importance of integrating advanced technologies such as AI, IoT, and deep learning in supporting sustainability, innovation, and smart city management. The results show that green technologies and innovations have great potential in creating more efficient and sustainable solutions in various sectors, whether in education, transportation, or urban management. This paper demonstrates that implementing advanced technologies in transportation systems yields significant positive outcomes across multiple domains: enhancing urban mobility efficiency, promoting sustainable development practices, and providing valuable frameworks for future smart city initiatives.